Analisis Propaganda Islamic State of Iraq and Syria (ISIS) di Indonesia Melalui Jalur Media Sosial - Eni Susanti; Andi Ismira; Sadriani (Hasanuddin Journal of International Affairs, 2023)
This study aims to analyze and understand how the ISIS network disseminated its extremist propaganda in Indonesia through social media between 2014 and 2017, as well as what mode of operation did the ISIS network use and how the propaganda was created and seek information about the methods and media used by the ISIS network. the strategies used, the intended audience, the discourses used, the messages and motivations conveyed, as well as the propaganda techniques used to create and spread the propaganda in a directed manner toward Indonesian society. The writing of this research uses a descriptive approach to analyze or present a comprehensive picture of the steps taken by the ISIS network to create and spread its extremist propaganda in Indonesia based on data observations. The type of data used is secondary data, and data collection techniques using a literature study approach, data collected from books, theses, papers, journals and websites. The results showed that the spread of Isis had started since January 2014 and 155 articles containing Isis propaganda had been recorded on the arrahman.com web page. not only web pages, Isis propaganda also wrote articles containing propaganda through Facebook social media accounts and also distributed them through the telegram chat application. From 2016–2017 there have been more than 60 telegram channels related to the spread of Isis ideology. Not only that, Isis also routinely publishes a digital bulletin in the Indonesian language called AL Fatihin which contains praise for the bomb terror that has been carried out in several radical Indonesian organizations.   Penelitian ini bertujuan untuk menganalisis dan memahami bagaimana jaringan ISIS menyebarluaskan propaganda ekstremisnya di Indonesia melalui media sosial antara tahun 2014 sampai 2017, serta mode operasi apa yang digunakan jaringan ISIS dan bagaimana propaganda tersebut dibuat dan mencari informasi tentang metode dan media yang digunakan oleh jaringan ISIS, strategi yang digunakan, audiens yang dituju, wacana yang digunakan, pesan dan motivasi yang disampaikan, serta teknik propaganda yang digunakan untuk membuat dan menyebarkan propagandanya secara terarah pada masyarakat Indonesia. Penulisan penelitian ini menggunakan pendekatan deskriptif untuk menganalisis atau menyajikan gambaran menyeluruh tentang langkah-langkah yang dilakukan jaringan ISIS untuk membuat dan menyebarluaskan propaganda ekstremisnya di Indonesia berdasarkan pengamatan data. Jenis data yang digunakan adalah data sekunder, dan teknik pengumpulan data dengan menggunakan pendekatan studi literatur, data dikumpulkan dari buku, tesis, makalah, jurnal dan website. Hasil penelitian menunjukkan bahwa penyebaran Isis sudah di mulai sejak januari 2014 dan sudah tercatat 155 tulisan berisi propaganda Isis di halaman web arrahman.com. tidak hanya halaman web, propganda Isis pun menulis tulisan berisis propaganda  melalui akun media sosial facebook dan disebarkan juga melalui melalui aplikasi chat telegram. Dari tahun 2016–2017 sudah terdapat lebih 60 channel telegram yang berkaitan dengan penyebaran ideologi Isis tersebut.Tidak hanya sampai situ, Isis juga rutin menerbitkan buletin digital berbahasa Indonesia yang bernama AL Fatihin yang berisi pujian–pujian atas teror bom yang telah di lakukan beberapa organisasi radikal Indonesia.